Cost leadership and bank internationalization - Rients Galema; Michael Koetter; Caroline Liesegang (Deutsche Bundesbank, 2013)
We adapt a theoretical model from the goods trade literature to test whether banks with a comparative cost advantage are more likely to enter foreign markets by means of foreign direct investment. We combine detailed proprietary bank-level data on the international activities of all German banks with publicly available bank micro data from possible destination markets to show that the decision to go abroad is driven by relative cost differences. Banks enter markets where they are cost leaders in terms of their marginal cost relative to those of banks in destination markets. They are attracted by markets that are larger and more competitive, as witnessed by lower interest rates charged by the most efficient competitors.
Keywords: F3; G21; 330; Trade in financial services; International banking; Productivity; Markups; Marginal costs